Establishing a core outcome set for mucopolysaccharidoses (MPS) in children: study protocol for a rapid literature review, candidate outcomes survey, and Delphi surveys - Howie, Alison H.; Tingley, Kylie; Inbar-Feigenberg, Michal; Mitchell, John J.; Butcher, Nancy J.; Offringa, Martin; Smith, Maureen; Angel, Kim; Gentle, Jenifer; Wyatt, Alexandra; Campeau, Philippe M.; Chan, Alicia; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Mucopolysaccharidoses (MPS) are a group of inherited metabolic diseases characterized by chronic, progressive multi-system manifestations with varying degrees of severity. Disease-modifying therapies exist to treat some types of MPS; however, they are not curative, underscoring the need to identify and evaluate co-interventions that optimize functioning, participation in preferred activities, and quality of life. A Canadian pediatric MPS registry is under development and may serve as a platform to launch randomized controlled trials to evaluate such interventions. To promote the standardized collection of patient/family-reported and clinical outcomes considered important to patients/families, health care providers (HCPs), and policymakers, the choice of outcomes to include in the registry will be informed by a core outcome set (COS). We aim to establish a patient-oriented COS for pediatric MPS using a multi-stakeholder approach. Methods In step 1 of the six-step process to develop the COS, we will identify relevant outcomes through a rapid literature review and candidate outcomes survey. A two-phase screening approach will be implemented to identify eligible publications, followed by extraction of outcomes and other pre-specified data elements. Simultaneously, we will conduct a candidate outcomes survey with children with MPS and their families to identify outcomes most important to them. In step 2, HCPs experienced in treating patients with MPS will be invited to review the list of outcomes generated in step 1 and identify additional clinically relevant outcomes. We will then ask patients/families, HCPs, and policymakers to rate the outcomes in a set of Delphi Surveys (step 3), and to participate in a subsequent consensus meeting to finalize the COS (step 4). Step 5 involves establishing a set of outcome measurement instruments for the COS. Finally, we will disseminate the COS to knowledge users (step 6). Discussion The proposed COS will inform the choice of outcomes to include in the MPS registry and, more broadly, promote the standardized collection of patient-oriented outcomes for pediatric MPS research. By involving patients/families from the earliest stage of the research, we will ensure that the COS will be relevant to those who will ultimately benefit from the research. Trial registration PROSPERO CRD42021267531 , COMET